INSTITUTIONAL MECHANISMS FOR REGULATING THE SPECIALIZATION OF AGRICULTURAL ENTERPRISES - ORISHCHENKO, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article addresses the issues of forming the specialization of agricultural enterprises, mainly studying the institutional mechanisms for regulating them. The purpose of the article is to analyze, systematize, and improve the existing theoretical and methodological framework regarding the formation of agricultural enterprise specialization and create a list of state regulation measures for the types of specialization of agricultural enterprises. The article examines the significance of specialization in agricultural production as a strategic tool for increasing resource utilization efficiency and ensuring the sustainable development of agricultural enterprises. The study justifies the importance of specialization for improving productivity, optimizing production processes, and reducing costs. It substantiates the types of specialization based on criteria such as sectoral focus (crop production, livestock, mixed specialization), production technology (traditional, innovative, and organic production), production scale (mass and niche specialization), and market integration level (export-oriented and local specialization). The article justifies the importance of institutional mechanisms for regulating specialization, such as state support, legislative initiatives, and financial tools that contribute to developing the agricultural sector. It is determined that state regulation of the agricultural sector aims to create favorable conditions for developing agricultural enterprises, ensure the country’s food security, support economic stability, and promote the sustainable development of rural areas. In turn, the regulation of agricultural enterprise specialization aims to increase production efficiency, maintain innovative technologies, ensure ecological safety, and stimulate the development of national agro-markets and exports. The article proposes directions for state regulation according to the types of agricultural enterprise specialization: in crop production – financial support, quotas, export programs, and environmental standards that ensure investment and productivity growth; in livestock – protection of producers’ rights, veterinary financing, and innovation that guarantee product safety and quality; in mixed specialization – support for the integration of production chains and energy efficiency that reduce costs; in organic production – certification standards, financial support, and marketing that promote the development of ecological agricultural production; in niche specialization – support for innovations and preferential financing for small and medium-sized enterprises; in export-oriented specialization – export standards, customs privileges, and support for trade relations to expand sales markets; in local specialization – support for local producers through market and infrastructure development, stimulating small businesses at the local level.